On the Sendov problem on the Whitney interpolation constant
For a function ƒ continuous on [0, 1] and satisfying the equalities \(f(0) = f( 13 ) = f( 23 ) = f(1) = 0,\) we prove that \(|f(x)| 2ω _4 ( 14,f ), x [0,1],\) where ω4(t,ƒ) is the fourth modulus of smoothness of the function ƒ., number=5, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Danilenko, I. G., year=1998, month=May, pages=732–734